AB0531 Real-world efficacy and safety of abatacept treatment for RA: 12-month interim analysis of the action study. (23rd January 2014) - Nüßlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H.M.; Boumpas, D.; Nurmohamed, M.T.; Bensen, W.G.; Burmester, G.R.; Peter, H.H.; Rainer, F.; Pavelka, K.; Chartier, M.; et al.
Abstract : Background: We previously presented 6-month (mth) results of a prospective, non-interventional study with IV abatacept (ABA); 1 here we show the efficacy, safety and retention rate (RR) results of a 12-mth planned interim analysis including 65% of the enrolled cohort. Objectives: To evaluate RR, efficacy and safety of ABA in RA patients (pts) treated in routine clinical practice. Methods: ACTION (AbataCepT In rOutiNe clinical practice) is a non-interventional, longitudinal study in ABA-treated RA pts. RR (Kaplan–Meier estimation; pts not reaching the timepoint were censored at the last infusion date available) and disease activity (DAS28 [ESR and/or CRP], CDAI, for pts with available data) are reported. Safety was assessed in all pts, and reported up to Aug 2011. Results: 1138/1114 pts were enrolled/evaluable. At 12 mths 65% of pts had reached the timepoint or discontinued, and were available for this analysis. Mean (SD) baseline characteristics were: age 56.5 (12.6) years (yrs); disease duration 11.0 (8.9) yrs;RF+ 69.2%; anti-CCP+ 65.2%; 70.0% with erosions; 89.4% had failed ≥1 biologic; 21.2% had received ABA monotherapy; 73.8% had concomitant corticosteroids. The 12-mth overall RR (95% CI) was 70.7% (67.5, 73.7); 81.6% (71.8, 88.5) in biologic-naïve pts, 69.4% (66.0, 72.7) in pts who had previously failed a biologic. 251 pts discontinued. Efficacy is shown in table 1 . Ninety-five SAEs were reported in 54/1138 (4.7%) pts (20 discontinuations): 8 deaths (4 due to serious infections), 19 serious infections, 8 malignancies, 5 cardiac and 3 vascular disorders. No TB, but one opportunistic infection was reported ( Pneumocystis jiroveci ). Conclusions: These long-term data confirm abatacept's clinical effectiveness, safety and RR in RA pts with long-term, erosive disease. These data are consistent with previous RCTs findings, 2, 3 the preliminary 6-mth findings, 1, 4 and national registry data for abatacept and other biologics. 5, 6 References: Nüßlein H et al. Ann Rheum Dis 2011. Genovese M et al. N Engl J Med 2005;353:1114–23. Kremer et al. Annals Internal Med 2006;144:865-76; Schiff M et al. Int J Clin Rheumatol 2010;5:581–91; Nüßlein H et al Ann Rheum Dis 2011;70(Suppl 3):464. Leffers HC et al. Ann Rheum Dis 2011;70:1216-22. Gomez-Reino J et al. Arthr Res Ther 2006;8:R29. Disclosure of Interest: H. Nüßlein Consultant for: Bristol-Myers Squibb, R. Alten Grant/Research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers Bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, M. Galeazzi: None Declared, H. Lorenz Grant/Research support from: Wyeth, Consultant for: Bristol-Myers Squibb, Wyeth/Pfizer, Essex, MSD, UCB, Chugai, Roche, Abbott, D. Boumpas: None Declared, M. Nurmohamed Grant/Research support from: BMS, MSD, Roche, Abbott, Pfizer and UCB, Consultant for: BMS, MSD, Roche, Abbott, Pfizer and UCB, Speakers Bureau: BMS, MSD, Roche, Abbott, Pfizer and UCB, W. Bensen Grant/Research support from: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Consultant for: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Speakers Bureau: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi -Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, G. Burmester Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, H. Peter: None Declared, F. Rainer: None Declared, K. Pavelka Consultant for: Roche, Abbott, MSD, Speakers Bureau: Pfizer, MSD, M. Chartier: None Declared, C. Poncet: None Declared, C. Rauch Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb